(untitled) (Transport systems and technologies, 2021)
The issue of determining the traction and energy characteristics of electric rolling stock with asynchronous traction drive is considered. It is noted that such rolling stock can work at any point of the traction area, resulting in the need to determine the characteristics of the rolling stock for the entire traction area. The calculation of the characteristics of the traction induction motor, which are the basis for determining the traction and energy characteristics of the electric rolling stock, is considered in detail. A procedure based on the calculation of the replacement circuit of an induction motor is proposed. The calculation of power losses due to higher harmonic voltages and currents is considered. An example of calculation of traction and energy characteristics of an DC electric shunting locomotive with a traction asynchronous electric drive is given.